Use of microwave technology in transdermal drug delivery / Nor Khaizan Anuar - Anuar, Nor Khaizan (2013)
The project focused on the use of microwave in controlling drug release from film matrix and modifying skin barrier for transdermal drug delivery. With reference to controlled-release application, the effects of microwave on drug release properties of pectin films carrying sulfanilamide (P-SN), sulfathiazole (P-ST) and sulfamerazine (P-SM) of high to low aqueous solubilities were investigated. These films were prepared by solvent-evaporation technique and treated by microwave at 80 W for 5 to 40 min Their profiles of drug dissolution, drug content, matrix interaction and matrix crystallinity were determined by drug dissolution testing, drug content assay,differential scanning calorimetry, X-ray diffractometry and scanning electron microscopy techniques. Microwave was found to be able to increase the matrix amorphousness. However, the strength of matrix interaction was accordingly increased thereby lowering the drug release propensity with a greater retardation extent in P-SN films. A gain in amorphous structure did not necessarily increase the drug release of film. Microwave can possibly retard drug release of pectin film carrying water-soluble drug through modulating its state of matrix interaction. In the case of skin barrier modification by microwave, the mechanism of microwave enhancing transdermal permeation of drug from film through its action on skin was investigated. The transdermal drug delivery profiles of pectin film was evaluated against pectin gel with reference to the influences of microwave, as well as chemical permeation enhancer namely oleic acid on skin. Hydrophilic P-SN films aid gels, with or without oleic acid (OA), were prepared and subjected to drug release and skin permeation studies. The skins were untreated or microwave treated, and characterized by infrared spectroscopy, raman spectroscopy, thermal, electron microscopy and histology techniques. Skin treatment by microwave at 2450 MHz for 5 min promoted drug permeation from OA-free film without incurring skin damage. Skin treatment by microwave followed by film loaded with drug and OA resulted in permeation of all drug molecules that were released from film. Microwave exerted spacing of lipid architecture of stratum comeum into structureless domains which was unattainable by OA. It allowed OA to permeate stratum comeum and accumulate in dermis at a greater ease, and synergistically inducing lipid/keratin fluidization at hydrophobic CH and hydrophilic O-H, N-H, C-O, C=0, C-N regimes of skin, and promoting drug permeation. Unlike solid film, skin treatment by microwave at 2450 MHz for 5 min demoted drug permeation from pectin gel. Formulation of gel with OA as penetration enhancer resulted in a greater reduction extent in drug permeation. Both OA and microwave exerted lipid/keratin fluidization at hydrophobic and hydrophilic regimes of skin. Using gel with freely soluble pectin molecules instead of solid film with entangled chains, these polymer molecules could interact with epidermis and dermis via hydrogen bonding to retard drug permeation. In comparison to microwave which fluidized stratum comeum into structureless domains, OA could extract endogenous lipid fraction and form separate phases within intercellular lipid lamellae. It provided a more extensive intercellular space for binding of pectin with skin, thereby remarkably decreasing drug permeation. The physical forms of a delivery system can exert opposite influences on transdermal drug permeation modulated by microwave or OA.